2015
DOI: 10.1021/acsami.5b02177
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Independent Proton Transport in Cerium(III) Phosphate Nanowires

Abstract: Understanding of water-related electrical conduction is of utmost importance in applications that utilize solid-state proton conductors. However, in spite of the vast amount of theoretical and experimental work published in the literature, thus far its mechanism remained unsolved. In this study, the structure-related ambient temperature electrical conduction of one-dimensional hydrophilic nanostructures was investigated. Cerium phosphate nanowires with monoclinic and hexagonal crystal structures were synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Cerium orthophosphate CePO 4 is a material with notable physicochemical properties that has received a fair amount of attention because of its multiple potential real-world applications. Due to mixed electrical conduction properties, CePO 4 has been proposed as a promising material for intermediate temperature fuel-cell and oxygen sensors applications. Photoluminescent terbium-doped CePO 4 is used in the fabrication of sensors for the detection of O 2 , Fe 2+ , Co 2+ , and glucose. Moreover, being a chemically stable material, CePO 4 is also a promising alternative to ZnO and TiO 2 in sunscreen filters for the protection of human skin from UV rays , and as a better additive for improved corrosion resistance of Ni–P coatings …”
Section: Introductionmentioning
confidence: 99%
“…Cerium orthophosphate CePO 4 is a material with notable physicochemical properties that has received a fair amount of attention because of its multiple potential real-world applications. Due to mixed electrical conduction properties, CePO 4 has been proposed as a promising material for intermediate temperature fuel-cell and oxygen sensors applications. Photoluminescent terbium-doped CePO 4 is used in the fabrication of sensors for the detection of O 2 , Fe 2+ , Co 2+ , and glucose. Moreover, being a chemically stable material, CePO 4 is also a promising alternative to ZnO and TiO 2 in sunscreen filters for the protection of human skin from UV rays , and as a better additive for improved corrosion resistance of Ni–P coatings …”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been provided toward the improvement of luminescent properties of CePO 4 nanomaterials doped with rare earth ions, and other hierarchical structures such as CePO 4 nanorods attached to cerium oxide (CeO 2 ) microcrystals, 17 CePO 4 nanorods decorated with quantum dots, 18 and CePO 4 @Gd:TbPO 4 core−shell structure 19 for the luminescent and bioimaging applications due to their unique optical property that emerges from the Ce 4f level transitions. Moreover, cerium phosphate and cerium oxide nanomaterials are well-known for their technological applications in sensors, 10,20 catalysis, 21,22 luminescent host materials, 23 fuel cells, 24 bioimaging, and biomedicine. 25 Highly reactive cerium assumes a trivalent Ce 3+ oxidation state in CePO 4 lattice, while it exists in tetravalent Ce 4+ state in the stoichiometric ceria structure in its bulk form.…”
Section: Introductionmentioning
confidence: 99%
“…9 They often have multiple crystal forms, cerium phosphate for example has two well documented crystal structures: rhabdophane (hexagonal) and monazite (monoclinic) with the hexagonal form usually including structural water, (CePO 4 .nH 2 O ) and formed at low temperatures while the monoclinic form is anhydrous and formed at high temperatures. The two forms of cerium phosphate show crystal specific properties, Pusztai et al 10 for example, demonstrated differences in the surface area and density of surface acidic sites between the hexagonal and monoclinic forms of cerium phosphate nanorods. They also showed a surface conductivity for the monoclinic form three times greater than that of the hexagonal form, accounted for by the observed differences in surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…Since the tuning of the crystal structure of the rare earth phosphates is often a matter of changing simple synthetic parameters such as pH, temperature, or pressure, [10][11][12][13] these materials offer interesting opportunities to optimise their performance for different applications. This is particularly true for heterogeneous catalysis where surface properties are key but it also applies in situations where growth of one phase on another is necessary.…”
Section: Introductionmentioning
confidence: 99%